2014
DOI: 10.1177/1090198114557124
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Social Support and Education With Breast and Cervical Cancer Screening

Abstract: Background. Disparities in breast and cervical cancer screening by socioeconomic status persist in the United States. It has been suggested that social support may facilitate screening, especially among women of low socioeconomic status. However, at present, it is unclear whether social support enables mammogram and Pap test compliance. Purpose. This study examines the association between social support and compliance with mammogram and Pap test screening guidelines, and whether social support provides added v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
46
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 45 publications
8
46
1
2
Order By: Relevance
“…Current smokers in our study population were also less likely to have initiated HPV vaccination. Further, the unvaccinated may have experienced a lower level of social support; social support has been shown to be associated with Pap test compliance [21]. Though not assessed in this study (pertinent questions not asked in all data years), another study noted that women who reported having routine Pap tests were more likely to have heard of HPV [22].…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Current smokers in our study population were also less likely to have initiated HPV vaccination. Further, the unvaccinated may have experienced a lower level of social support; social support has been shown to be associated with Pap test compliance [21]. Though not assessed in this study (pertinent questions not asked in all data years), another study noted that women who reported having routine Pap tests were more likely to have heard of HPV [22].…”
Section: Resultsmentioning
confidence: 91%
“…Given that younger women were closer to the recommended age for routine HPV vaccination [13] and older women may have had a pre-established routine of Pap testing, we accounted for age (21)(22)(23)(24)(25)(26)(27)(28)(29)(30). We defined race/ethnicity as four categories: non-Hispanic [NH] White, NH Black, Hispanic, Asian/NH other (89.3% Asian).…”
Section: Covariatesmentioning
confidence: 99%
“…Husband support helped his wife solve pressure and effect about their health status and clinical assessment by direct path shown on health belief model theory. 21,29 Women who had support from their husband were more likely to take screening by 3.05 times compared to women who did not have support from their husband. 30,31 The problem addressed the involvement and participation from men, but this case was very inadequate because women's health was imposed for their self-awareness-culture, economic factor, and knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Being married or living with a partner is also associated with participation in cancer screening;12, 13 however, evidence is conflicting with some studies finding no association or an inverse association between social connectedness and engagement in preventive health services 14, 15, 16. Marital status has been a focus of these studies, with the functional dimension having received much less attention than has the structural dimension, and studies of social support primarily only include women 17, 18. Studies are predominantly cross-sectional, and, to our knowledge, length of exposure to or dynamics of social connectedness, which might be important in mid-to-late adulthood with changing employment and social roles, have not been explored in relation to preventive health care.…”
Section: Introductionmentioning
confidence: 99%